Positive electrode active material and lithium secondary battery including same

By using molten salt and metal oxide dopants in the precursor calcining step of the lithium secondary battery, uniform particle growth is solved, and the challenges of lithium secondary battery in terms of high capacity and low rate performance are achieved to improve the capacity and life performance of lithium secondary battery.

CN119890289APending Publication Date: 2025-04-25ECOPRO BM CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411341617.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-25
Filing Date
2024-09-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing lithium secondary batteries have challenges in high capacity and low rate performance, especially while maintaining high reversible capacity, it is difficult to improve the rate performance and life performance of nickel-based lithium composite oxides.

Method used

By combining the molten salt-based flux and metal oxide-based dopants in the precursor calcination step, uniform particle growth is induced, interparticle aggregation phenomenon is reduced, and harsh calcination conditions and crushing processes are avoided, thereby obtaining a single crystal positive electrode active material with uniform particle size distribution and high sharpness.

Benefits of technology

The capacity and life performance of lithium secondary batteries are improved, and the degradation speed and cost of the battery are reduced by obtaining a high sharp particle size distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890289A_ABST
    Figure CN119890289A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material and a lithium secondary battery comprising the same, and more specifically, to a single crystal type positive electrode active material in which a particle size distribution peak observed in a volume cumulative particle size distribution diagram shifts to a Dmax side, which is the maximum particle size, and the sharpness of the particle size distribution peak is high, and a lithium secondary battery comprising the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material and a lithium secondary battery including the same, and more particularly to a particle size distribution peak observed in a volume cumulative particle size distribution diagram toward D as the maximum particle size. max A single crystal positive electrode active material and a lithium secondary battery comprising the same having a side shift and a high sharpness of the particle size distribution peak. Background Art

[0002] Batteries use materials that can undergo electrochemical reactions at the positive and negative electrodes to store electrical energy. A typical example of such batteries is a lithium secondary battery that stores electrical energy through the chemical potential difference when lithium ions are inserted / released between the positive and negative electrodes.

[0003] The lithium secondary battery is prepared by using a substance capable of reversibly inserting and extracting lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Lithium composite oxides are used as positive electrode active materials for lithium secondary batteries, and for example, composite oxides such as LiCoO2, LiMN2O4, LiNiO2, and LiMnO2 are currently under study.

[0005] Among the above-mentioned positive electrode active materials, LiCoO2 is the most widely used due to its excellent life characteristics and charge and discharge efficiency, but has the disadvantage of limited price competitiveness because cobalt used as a raw material is expensive.

[0006] Lithium manganese-based oxides such as LiMnO2 and LiMN2O4 have the advantages of excellent thermal stability and low price, but have the problems of small capacity and poor high temperature characteristics. In addition, LiNiO2-based positive electrode active materials have battery characteristics of high discharge capacity, but due to the active cation mixing between lithium and nickel, it is not only difficult to synthesize, but also has the problem that the rate performance and life performance of the synthesized positive electrode active materials are very low.

[0007] Accordingly, in order to improve the low rate performance and life performance while maintaining the high reversible capacity of LiNiO2, the so-called ternary type, the so-called NCM (Ni-Co-Mn) and NCA (Ni-Co-Al) ternary type or NCMA (Ni-Co-Mn-Al) quaternary type lithium composite oxides such as ternary type in which a part of nickel is replaced by cobalt, manganese and / or aluminum have been developed. Since the lower the nickel content in the ternary or quaternary lithium composite oxide as described above, the lower the reversible capacity, therefore, recently, active research has been conducted to increase the nickel content in the lithium composite oxide.

[0008] In addition, it is reported that the general ternary or quaternary lithium composite oxide has a secondary particle form formed by the aggregation of tens to hundreds or more primary particles, and as the number of primary particles constituting the secondary particles decreases, the stability (life performance, etc.) of the positive electrode active material can be improved. The lithium composite oxide with a reduced number of primary particles as described above is also called a lithium composite oxide with a single crystal structure or a lithium composite oxide with a single particle structure.

[0009] For example, Journal of The Electrochemical Society (Volume 164, Issue 7, A1534-A1544, Published on May 23, 2017) discloses a lithium composite oxide (LiNi 0.5 Mn 0.3 Co 0.2 The stability of lithium ions is somewhat improved compared with that of polycrystalline lithium composite oxides with the same composition.

[0010] However, as disclosed in the above literature, when the calcination temperature is excessively increased to crystallize the lithium composite oxide constituting the positive electrode active material, or the amount of lithium relative to the transition metal in the lithium composite oxide is excessively increased, cation mixing in the crystal structure may increase.

[0011] In particular, when the cation mixing phenomenon in the lithium composite oxide having a single crystal structure increases, the surface resistance characteristics of the lithium composite oxide change with a phase other than a layered crystal structure (eg, a rock-salt phase, etc.), or may cause premature degradation.

[0012] Furthermore, when single crystallization of lithium composite oxide is induced simply by severe calcination conditions (eg, over-calcination at a high calcination temperature), it is difficult to induce uniform particle growth, and thus particles may agglomerate, making it difficult to obtain a positive electrode active material having a uniform particle size distribution.

[0013] In addition, after synthesizing secondary particles formed by agglomeration of multiple primary particles, a positive electrode active material including a lithium composite oxide with a single crystal structure can be prepared by a pulverization process. However, not only does the pulverization process cause a sharp increase in the processing cost of the positive electrode active material, but the surface of the lithium composite oxide may also be damaged during the pulverization process. As described above, the defects present on the surface of the lithium composite oxide can change the surface resistance characteristics of the lithium composite oxide. In addition, gas may be generated by side reactions with the electrolyte through the above-mentioned surface defects, and cracks may appear along the above-mentioned surface defects.

[0014] Therefore, it is necessary to develop a single-crystal positive electrode active material that can have a uniform particle size distribution without an additional pulverization process after precursor calcination by inducing uniform particle growth and reducing inter-particle agglomeration.

[0015] Prior art literature

[0016] Non-patent literature

[0017] (Non-patent document 1) Journal of The Electrochemical Society, Vol. 164, No. 7, A1534-A1544 (published on May 23, 2017) Summary of the invention

[0018] Technical issues

[0019] In the lithium secondary battery market, while the growth of lithium secondary batteries for electric vehicles plays a leading role in the market, the demand for positive electrode active materials used in lithium secondary batteries is also changing.

[0020] For example, in the prior art, lithium secondary batteries using lithium iron phosphate (LFP) are mainly used from the viewpoint of ensuring safety, but recently, the use of nickel-based lithium composite oxides having a larger energy capacity per unit weight than LFP is expanding (of course, relatively cheap LFP is still used at present to reduce costs).

[0021] In addition, nickel-based lithium composite oxides, which are recently mainly used as positive electrode active materials for high-capacity lithium secondary batteries, generally have a ternary type composition such as NCM (Ni-Co-Mn) and NCA (Ni-Co-Al) or a quaternary type composition such as NCMA (Ni-Co-Mn-Al).

[0022] As described above, in order to achieve high capacity of the ternary or quaternary nickel-based lithium composite oxide, the stability (life performance, etc.) of the positive electrode active material can be improved as the number of primary particles constituting the secondary particles is reduced.

[0023] However, according to the commercial process so far, the crystal structure of the lithium composite oxide may change due to the harsh calcination conditions. In addition, since it is difficult to induce uniform particle growth under harsh calcination conditions, it is inevitably accompanied by a pulverization process, resulting in a problem of rapidly increasing processing costs of positive electrode active materials.

[0024] Therefore, an object of the present invention is to provide a single crystal positive electrode active material having a uniform particle size distribution by inducing uniform particle growth without harsh calcination conditions and pulverization processes and reducing inter-particle agglomeration phenomena.

[0025] Another object of the present invention is to provide a positive electrode active material having a highly sharp particle size distribution due to uniform particle growth and reduced inter-particle aggregation.

[0026] In addition, the present invention aims to provide a particle size distribution peak observed in a volume cumulative particle size distribution diagram, which is D as the maximum particle size. max The particle size distribution peak is shifted to the side and the sharpness of the particle size distribution peak is relatively high in the single crystal positive electrode active material.

[0027] In addition, another object of the present invention is to provide a lithium secondary battery using the positive electrode active material defined herein.

[0028] The purpose of the present invention is not limited to the purpose mentioned above, and other purposes and advantages of the present invention not mentioned can be understood through the following description, and can be more clearly understood through the embodiments of the present invention. In addition, it can be easily understood that the purpose and advantages of the present invention can be achieved by the means and combinations thereof in the claims.

[0029] Solutions to the problem

[0030] Therefore, according to one aspect of the present invention, a positive electrode active material is provided. The positive electrode active material is a positive electrode active material including a lithium composite oxide capable of inserting and extracting lithium, and the lithium composite oxide satisfies the following formula 1 and formula 2.

[0031] [Formula 1]

[0032] D max ≤15μm

[0033] [Formula 2]

[0034] D 90 -D 50 >D 50 -D 10

[0035] (In the above formula 1 and formula 2, in the volume cumulative particle size distribution diagram obtained by laser diffraction particle size distribution measurement, the particle size of 10% of the volume cumulative amount is D 10 , the particle size at which 50% of the volume accumulation occurs is D 50 , the particle size at which 90% of the volume accumulation occurs is D 90 The minimum particle size of the above volume cumulative particle size distribution diagram is D min The maximum particle size of the above volume cumulative particle size distribution diagram is D max ).

[0036] The lithium composite oxide constituting the positive electrode active material according to the above-described embodiment may be a single crystal type having a uniform particle size distribution and a high particle size distribution sharpness.

[0037] In one embodiment, the D of the lithium composite oxide 50 The average particle size is 3 μm to 9 μm, and the lithium composite oxide may satisfy at least one, at least two, at least three or all of the following formulas 3 to 6.

[0038] [Formula 3]

[0039] 4.2μm <D 90 -D 50 <8.2μm

[0040] [Formula 4]

[0041] 2μm <D 50 -D 10 <4μm

[0042] [Formula 5]

[0043] 1.2≤(D 90 -D 10 ) / D 50 ≤1.5

[0044] [Formula 6]

[0045] 1.2≤(D max -D 50 ) / (D 50 -D min )≤2.7

[0046] In one embodiment, the lithium composite oxide contains at least lithium and a transition metal. For example, the lithium composite oxide may be a lithium nickel-based composite oxide containing at least lithium and nickel. The transition metal may include at least one, at least two, at least three or all selected from nickel, cobalt, manganese and aluminum.

[0047] The lithium composite oxide may be represented by Chemical Formula 1 below.

[0048] [Chemical formula 1]

[0049] Li a Ni 1-(b+c+d) Co b M1 c M2 d O2

[0050] (Wherein, M1 is at least one selected from Mn and Al, M2 is at least one selected from Na, K, Mg, Ca, Ba, Mn, B, Ce, Hf, Ta, Cr, F, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd and Cu, M1 and M2 are different from each other, 0.5≤a≤1.5, 0≤b≤0.20, 0≤c≤0.30, 0≤d≤0.10).

[0051] In one embodiment, the lithium composite oxide may be present in at least one form selected from a single particle and a secondary particle formed by agglomeration of a plurality of primary particles. In addition, the secondary particle may be in a state of agglomeration of one to ten primary particles.

[0052] Furthermore, according to another aspect of the present invention, a positive electrode including the positive electrode active material is provided.

[0053] According to still another aspect of the present invention, there is provided a lithium secondary battery using the positive electrode.

[0054] Effects of the Invention

[0055] According to the present invention, a positive electrode active material is prepared by inducing uniform particle growth without harsh calcination conditions and pulverization processes by combining a molten salt-based flux and a metal oxide-based dopant in a precursor calcination step, thereby preventing inter-particle agglomeration phenomenon.

[0056] In the positive electrode active material according to the present invention, the particle size distribution peak observed in the volume cumulative particle size distribution diagram is oriented toward D which is the maximum particle size. max The particle size distribution peak has a higher sharpness, and a lithium secondary battery using the positive electrode active material having the particle size distribution characteristics as described above can have improved capacity performance and life performance.

[0057] In addition to the above-described effects, specific effects of the present invention will be described while explaining specific details for implementing the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 is a SEM image of the positive electrode active material according to Example 1.

[0059] Figure 2 is a SEM image of the positive electrode active material according to Example 2.

[0060] Figure 3 is a SEM image of the positive electrode active material according to Example 3.

[0061] Figure 4is a SEM image of the positive electrode active material according to Comparative Example 1.

[0062] Figure 5 is a SEM image of the positive electrode active material according to Comparative Example 2.

[0063] Figure 6 is a SEM image of the positive electrode active material according to Comparative Example 3. DETAILED DESCRIPTION

[0064] Specific terms are defined herein for ease of understanding. Unless specifically defined herein, scientific terms and technical terms used herein should have the meanings commonly understood by those skilled in the art. In addition, it should be understood that as used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form, and vice versa.

[0065] Positive active material

[0066] A positive electrode active material according to one aspect of the present invention includes a lithium composite oxide capable of ion insertion / deintercalation of lithium ions.

[0067] The lithium composite oxide is a composite metal oxide capable of inserting and extracting lithium ions and has a layered crystal structure belonging to the R-3m space group. The lithium composite oxide having a layered crystal structure exhibits a characteristic peak in the region of 2θ of 18° to 20° in a diffraction pattern obtained by XRD analysis.

[0068] In one embodiment, the lithium composite oxide contains at least lithium and a transition metal. The transition metal may include at least one, at least two, at least three or all selected from nickel, cobalt, manganese and aluminum.

[0069] Preferably, the lithium composite oxide may be a lithium nickel-based composite oxide containing nickel. Alternatively, the lithium composite oxide may be a lithium nickel-based composite oxide containing nickel and cobalt.

[0070] In one embodiment, LiNiO2, in order to improve the low rate performance and life performance while maintaining high reversible capacity, the above-mentioned lithium nickel-based composite oxide may be a ternary type such as NCM (Ni-Co-Mn) and NCA (Ni-Co-Al) or a quaternary type lithium composite oxide such as NCMA (Ni-Co-Mn-Al) in which a portion of nickel is replaced by cobalt, manganese and / or aluminum. The above-mentioned ternary or quaternary lithium composite oxide may further include dopants other than nickel, cobalt, manganese and aluminum. In another embodiment, the above-mentioned lithium nickel-based composite oxide may be a cobalt-free lithium composite oxide that does not contain cobalt in the bulk particles. The above-mentioned cobalt-free lithium composite oxide may also contain dopants other than nickel, cobalt, manganese and aluminum.

[0071] In one embodiment, the lithium composite oxide may be represented by the following Chemical Formula 1.

[0072] [Chemical formula 1]

[0073] Li a Ni 1-(b+c+d) Co b M1 c M2 d O2

[0074] Among them, M1 is at least one selected from Mn and Al, M2 is at least one selected from Na, K, Mg, Ca, Ba, Mn, B, Ce, Hf, Ta, Cr, F, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd and Cu, M1 and M2 are different from each other, 0.5≤a≤1.5, 0≤b≤0.20, 0≤c≤0.30, 0≤d≤0.10.

[0075] a, which represents the ratio of lithium to all elements other than lithium (Ni+Co+M1+M2) in the lithium composite oxide, may be 0.5 to 1.5, 0.75 to 1.25, 0.90 to 1.1, or 0.95 to 1.05.

[0076] In one embodiment, the lithium composite oxide may be a lithium nickel-based composite oxide having a molar fraction of nickel of 70% or more relative to all elements other than lithium in the lithium composite oxide. In this case, in Chemical Formula 1, b+c+d is 0.30 or less. That is, the lithium composite oxide according to the embodiment is a lithium nickel-based composite oxide having a molar fraction of nickel of 70% or more relative to all elements other than lithium and having a layered crystal structure belonging to the R-3m space group.

[0077] In addition, according to another embodiment, the molar fraction of nickel relative to all elements other than lithium in the above-mentioned lithium composite oxide is greater than 75% (in this case, b+c+d is less than 0.25), greater than 80% (in this case, b+c+d is less than 0.20), greater than 85% (in this case, b+c+d is less than 0.15) or greater than 90% (in this case, b+c+d is less than 0.10).

[0078] When the lithium composite oxide contains cobalt, the molar fraction of cobalt relative to all elements other than lithium in the secondary particles may be 20% or less, 15% or less, 10% or less, or 5% or less. When the lithium composite oxide contains cobalt, b in the chemical formula 1 is greater than 0, and when the lithium composite oxide is a cobalt-free lithium composite oxide that does not contain cobalt, b in the chemical formula 1 is 0.

[0079] When the lithium composite oxide contains manganese and / or aluminum, the molar fraction of manganese and / or aluminum relative to all elements other than lithium in the lithium composite oxide may be 30% or less, 20% or less, 15% or less, 10% or less, or 5% or less. When the lithium composite oxide contains manganese and / or aluminum, c in the chemical formula 1 is greater than 0.

[0080] In the above chemical formula 1, M2 refers to a dopant present in the above secondary particles. The above dopant may be present in the lattice of the above primary particles in a doped state. In addition, in the above chemical formula 1, M2 may optionally include an element derived from a molten salt flux used in the step of calcining the precursor of the above lithium composite oxide and / or a metal oxide dopant.

[0081] When the lithium composite oxide includes a dopant, d in the chemical formula 1 is greater than 0, and when the lithium composite oxide does not include a dopant, d in the chemical formula 1 is 0.

[0082] In addition, the content of dopants of all elements except lithium in the secondary particles is less than the content of nickel, cobalt and M1. For example, the molar fraction of dopants of all elements except lithium in the secondary particles may be less than 10%, less than 5%, less than 4%, less than 3%, less than 2%, less than 1%, less than 0.5%, less than 0.4%, less than 0.3%, less than 0.2% or less than 0.1%.

[0083] When the secondary particles selectively contain dopants, the dopants may include at least one selected from Na, K, Mg, Ca, Ba, Mn, B, Ce, Hf, Ta, Cr, F, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd and Cu.

[0084] The upper and lower limits of the contents of nickel, cobalt, M1, and M2 defined in the above Chemical Formula 1 may be appropriately selected within the range satisfying the above definitions.

[0085] The lithium composite oxide may exist in at least one form selected from a single particle and a secondary particle formed by the agglomeration of a plurality of primary particles. Therefore, the positive electrode active material may exist as an aggregate of a single particle and a secondary particle. However, when the inter-particle agglomeration phenomenon is reduced by inducing uniform particle growth during the preparation of the positive electrode active material, the ratio of the single particle to the secondary particle in the aggregate increases, thereby having a more uniform particle size distribution, and in particular, a positive electrode active material having a high sharpness of the particle size distribution can be obtained. When a positive electrode active material having a high sharp particle size distribution as described above is used, the capacity performance and life performance of the lithium secondary battery can be improved. Among them, a narrow width of the particle size distribution peak confirmed from the volume cumulative particle size distribution diagram can mean that the sharpness of the particle size distribution is high.

[0086] When the single particles are aggregated and exist as secondary particles, each single particle constituting the secondary particles may be referred to as a primary particle. At this time, the composition of the single particles, the primary particles, and the secondary particles may all be represented by the chemical formula 1. In addition, the single particles, the primary particles, and the secondary particles all exist as particles capable of inserting / extracting lithium.

[0087] The above-mentioned single particle and the above-mentioned primary particle may have a rod (rod) shape, an elliptical shape and / or an irregular shape. In addition, unless specially designed in the preparation process, primary particles of various shapes may exist in the same positive electrode active material. In addition, the above-mentioned primary particle refers to a particle unit that does not have a grain boundary in appearance when observed with a scanning electron microscope at a magnification of 5000 to 20000 times.

[0088] The average particle size of the single particle and the primary particle may be 0.5 μm to 10 μm, 0.5 μm to 8 μm, 0.5 μm to 6 μm, 0.5 μm to 5 μm, 1 μm to 10 μm, 1 μm to 8 μm, 1 μm to 6 μm, 1 μm to 5 μm, 2 μm to 10 μm, 2 μm to 8 μm, 2 μm to 6 μm or 2 μm to 5 μm. At this time, as the average particle size of the primary particle of the single particle, the average value of the length in the major axis direction and the length in the minor axis direction of the single particle and the primary particle ([major axis length + minor axis length] / 2) may be used.

[0089] The lithium composite oxide is a single crystal lithium composite oxide, wherein the single crystal refers to a single particle or a primary particle as the smallest particle unit constituting the lithium composite oxide existing as a single crystal grain.

[0090] When secondary particles are present in the polymer, the average particle size of the secondary particles may be 0.5 μm to 15 μm, 1.0 μm to 12 μm, 1.0 μm to 10 μm, 2.0 μm to 12 μm, or 2.0 μm to 10 μm. The average particle size of the secondary particles may be calculated as the average value of the particle sizes of the secondary particles confirmed by the SEM image. The average particle size of the secondary particles may vary depending on the number of the primary particles constituting the secondary particles.

[0091] The particle size distribution of the lithium composite oxide in the positive electrode active material can be measured using a laser diffraction method. For example, after the secondary particles are dispersed in a dispersion medium, they are introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiated with an ultrasonic wave of about 28kHz at a power of 60W, and then after obtaining a volume cumulative particle size distribution chart, the particle sizes corresponding to 10%, 50%, and 90% of the volume cumulative amount, the minimum particle size of the volume cumulative particle size distribution chart, and the maximum particle size of the volume cumulative particle size distribution chart can be calculated.

[0092] The particle size corresponding to 50% of the cumulative volume is defined as the average particle size (D 50 ). In addition, based on the volume cumulative particle size distribution diagram obtained by laser diffraction particle size distribution measurement, the particle size at which 10% of the volume cumulative amount is defined as D 10 The particle size at which 50% of the volume accumulation is defined as D 50 The particle size at which 90% of the volume accumulation occurs is defined as D 90 The minimum particle size of the above volume cumulative particle size distribution diagram is defined as D min The maximum particle size of the above volume cumulative particle size distribution diagram is defined as D max .

[0093] In one embodiment, the D of the lithium composite oxide 50 It may be 3 μm to 9 μm, 3 μm to 8 μm, 4 μm to 8 μm, 4 μm to 7 μm, or 5 μm to 7 μm.

[0094] In addition, the D of the above lithium composite oxide min It may be 0.5 μm to 4 μm, 1 μm to 4 μm, 1.6 μm to 3.5 μm, 2 μm to 3.2 μm or 2 μm to 2.8 μm, D 10 It can be 1 μm to 4 μm, 2 μm to 4 μm, 2.5 μm to 3.5 μm or 2.7 μm to 3.3 μm, D 90 It may be 6 μm to 15 μm, 8 μm to 14 μm, or 9 μm to 12 μm.

[0095] As defined above, D min , D 10 , D 50 , D 90 and D max The upper limit and the lower limit of can be appropriately selected within the range satisfying the following Formulas 1 to 6.

[0096] The following Formulas 1 to 6 are calculated based on aggregates including single particles and secondary particles.

[0097] In the positive electrode active material, the lithium composite oxide satisfies the following Formula 1.

[0098] [Formula 1]

[0099] D max ≤15μm

[0100] The fact that the maximum particle size of the lithium composite oxide obtained in the volume cumulative particle size distribution diagram of the positive electrode active material exceeds 15 μm means that the growth of single particles and secondary particles constituting the positive electrode active material is excessively induced.

[0101] When the growth of the single particles constituting the above-mentioned positive electrode active material and the primary particles constituting the secondary particles is excessively induced, as the lithium ion diffusivity through the above-mentioned single particles and the above-mentioned primary particles decreases, the capacity and output of the lithium secondary battery using the above-mentioned positive electrode active material may decrease. In addition, as the resistance increases due to the excessive growth of the above-mentioned single particles and the above-mentioned primary particles, polarization may occur, and cracks may be generated in the particles due to the above-mentioned polarization phenomenon, which ultimately leads to a reduction in the life of the above-mentioned positive electrode active material.

[0102] When the maximum particle size of the lithium composite oxide exceeds 15 μm, it is difficult for the particle size distribution peak observed in the volume cumulative particle size distribution diagram to be oriented toward D, which is the maximum particle size. max It is difficult to obtain a single-crystal positive electrode active material having a sharp peak in the particle size distribution.

[0103] The D of the above lithium composite oxide max It may be 15 μm or less, 14.5 μm or less, or 14.4 μm or less.

[0104] [Formula 2]

[0105] D 90 -D 50 >D 50 -D 10

[0106] According to the above formula 2, D 90 -D 50 Than D 50 -D 10A larger value means that in the above volume cumulative particle size distribution diagram of the positive electrode active material, D 50 Than D 90 Closer to D 10 Therefore, in the above volume cumulative particle size distribution diagram of the positive electrode active material, when D max ≤15μm, and D 50 Than D 90 Closer to D 10 When the volume cumulative particle size distribution diagram is observed, the particle size distribution peaks toward D as the maximum particle size. max The particle size distribution peak of the single crystal positive electrode active material is shifted to the side, thereby obtaining the above-mentioned particle size distribution peak with high sharpness.

[0107] According to the present invention, in the calcination step of the above-mentioned lithium composite oxide precursor, by combining the use of molten salt flux and metal oxide dopant, uniform particle growth can be induced even in the absence of harsh calcination conditions and pulverization processes, thereby obtaining a positive electrode active material with reduced inter-particle agglomeration phenomenon.

[0108] The positive electrode active material obtained by the above process has a uniform particle size distribution, and in particular has a particle size distribution peak observed in the volume cumulative particle size distribution diagram with a maximum particle size D max When a positive electrode active material showing these particle size distribution characteristics is used, the capacity performance and life performance of a lithium secondary battery can be improved.

[0109] As described above, the particle size distribution is uniform, and the particle size distribution peak is oriented toward D as the maximum particle size. max The positive electrode active material having a side-shifted particle size distribution peak with high sharpness preferably satisfies both Formula 1 and Formula 2.

[0110] In order to improve the uniformity of the particle size distribution of the lithium composite oxide in the positive electrode active material, the peak of the particle size distribution is directed to D max The above-mentioned lithium composite oxide may satisfy at least one, at least two, at least three or all of the following formulas 3 to 6.

[0111] [Formula 3]

[0112] 4.2μm <D 90 -D 50 <8.2μm

[0113] [Formula 4]

[0114] 2μm <D 50 -D 10 <4μm

[0115] D 90-D 50 It may be greater than 4.2 μm and less than 8.2 μm, greater than 4.2 μm and less than or equal to 7.5 μm, greater than 4.2 μm and less than or equal to 7.0 μm, greater than or equal to 4.3 μm and less than or equal to 6.5 μm, or greater than or equal to 4.38 μm and less than or equal to 6.21 μm. 90 -D 50 The upper limit and lower limit of can be arbitrarily combined within the range satisfying the above formula 1 and formula 2.

[0116] D 50 -D 10 It may be greater than 2 μm and less than 4 μm, greater than or equal to 2.2 μm and less than or equal to 3.8 μm, greater than 2.4 μm and less than or equal to 3.6 μm, greater than or equal to 2.6 μm and less than or equal to 3.5 μm, or greater than or equal to 2.62 μm and less than or equal to 3.48 μm. 50 -D 10 The upper limit and lower limit of can be arbitrarily combined within the range satisfying the above formula 1 and formula 2.

[0117] When D 90 -D 50 and D 50 -D 10 When equations 3 and 4 are satisfied, the particle size distribution peak observed in the volume cumulative particle size distribution diagram can be obtained as the maximum particle size D max The positive electrode active material is offset to the side. 90 -D 50 and D 50 -D 10 The range of can also be arbitrarily combined within the range satisfying the above formula 1 and formula 2.

[0118] [Formula 5]

[0119] 1.2≤(D 90 -D 10 ) / D 50 ≤1.5

[0120] In the positive electrode active material having a particle size distribution satisfying Formula 1 and Formula 2, (D 90 -D 10 ) / D 50 It indicates the degree of deviation of the particle size distribution peak observed in the volume cumulative particle size distribution diagram. 90 -D 10 ) / D 50 When it is less than 1.2, the particle size distribution peak observed in the volume cumulative particle size distribution diagram is toward D as the maximum particle size. max On the other hand, when (D 90 -D10 ) / D 50 When it is greater than 1.5, this means that the particle size distribution peak observed in the volume cumulative particle size distribution diagram has almost no peak toward D which is the maximum particle size. max Side offset.

[0121] According to the above formula 5 (D 90 -D 10 ) / D 50 It may be 1.2 to 1.5, 1.2 to 1.48, or 1.21 to 1.48.

[0122] [Formula 6]

[0123] 1.2≤(D max -D 50 ) / (D 50 -D min )≤2.7

[0124] In the positive electrode active material having a particle size distribution satisfying Formula 1 and Formula 2, (D max -D 50 ) / (D 50 -D min ) refers to the sharpness of the particle size distribution peak observed in the volume cumulative particle size distribution diagram. max -D 50 ) / (D 50 -D min ) is less than 1.2, which means that the sharpness of the particle size distribution peak observed in the volume cumulative particle size distribution diagram is too high.

[0125] On the other hand, when (D max -D 50 ) / (D 50 -D min ) is greater than 2.7, which means that the uniformity of the particle size distribution observed in the volume cumulative particle size distribution diagram and the sharpness of the particle size distribution peak are low. If the uniformity of the particle size distribution and the sharpness of the particle size distribution peak are too high or too low, the energy density per unit volume is likely to decrease.

[0126] In order to improve the uniformity of the particle size distribution and the sharpness of the particle size distribution peak observed in the volume cumulative particle size distribution diagram, (D max -D 50 ) / (D 50 -D min ) can be 1.2 or more and 2.7 or less, 1.3 or more and 2.6 or less, 1.4 or more and 2.5 or less, 1.5 or more and 2.4 or less, or 1.59 or more and 2.32 or less.

[0127] As described above, the lithium composite oxide may exist in at least one form selected from a single particle and a secondary particle formed by agglomeration of a plurality of primary particles, and therefore, the positive electrode active material may exist as an aggregate of a single particle and a secondary particle. That is, the positive electrode active material may be defined as an aggregate of a plurality of lithium composite oxides having the same and / or different grain boundary densities.

[0128] The grain boundary density can be calculated by substituting the number of primary particles (P) located on a virtual straight line (L) passing through the center of the lithium composite oxide in the long-axis direction in the cross-sectional SEM image of the lithium composite oxide into the following formula 7.

[0129] [Formula 7]

[0130] Grain boundary density = (the number of interfaces (B) between primary particles located on the above-mentioned imaginary straight line (L) / the number of primary particles (P) located on the above-mentioned imaginary straight line (L))

[0131] For example, when the lithium composite oxide is a single particle, the number of interfaces (grain boundaries) between primary particles located on the imaginary straight line is 0, so the grain boundary density value may be 0. On the other hand, when the number of primary particles (P) located on the imaginary straight line (L) is two and the number of interfaces (B) between primary particles located on the imaginary straight line (L) is one, the grain boundary density value may be 0.5.

[0132] As the average grain boundary density of the lithium composite oxide present in the aggregate approaches 0, the ratio of the lithium composite oxide present as a single particle in the aggregate increases compared to the secondary particles.

[0133] In addition, the lithium composite oxide present as secondary particles in the aggregate may be in a state where 2 to 100, 2 to 50, 2 to 30, 2 to 20, or 2 to 10 primary particles are aggregated.

[0134] In addition, as defined herein, when the positive electrode active material subjected to grain growth is subjected to X-ray diffraction analysis using Cu-Kα rays, the following characteristics may be exhibited.

[0135] In one embodiment, when the positive electrode active material is subjected to X-ray diffraction analysis using Cu-Kα rays, the full width at half maximum (FWHM) of the diffraction peak attributable to the (104) plane can be greater than 0.080 and less than 0.11, greater than 0.081 and less than 0.11, greater than 0.082 and less than 0.10, greater than 0.082 and less than 0.095, or greater than 0.083 and less than 0.090.

[0136] If the full width at half maximum of the diffraction peak attributable to the (104) plane is less than 0.080, the size of the grain along the (104) plane calculated according to the Scherrer equation may be larger than the desired size. On the other hand, if the full width at half maximum of the diffraction peak attributable to the (104) plane is greater than 0.11, the growth of the grain along the (104) plane calculated according to the Scherrer equation is insufficient, resulting in insufficient conductivity of lithium ions.

[0137] Furthermore, when the positive electrode active material is subjected to X-ray diffraction analysis using Cu—Kα radiation, the full width at half maximum of the diffraction peak attributed to the (003) plane may be 0.080 to 0.10 or 0.085 to 0.095.

[0138] In addition, the c-axis length of the crystallites obtained by Rietveld analysis of X-ray diffraction of the positive electrode active material can be Below or the following.

[0139] The crystallite size obtained by Rietveld analysis of X-ray diffraction of the positive electrode active material may be 147 nm to 162 nm, 150 nm to 162 nm, or 150 nm to 161.5 nm.

[0140] If the grains and / or primary particles constituting the single particles and secondary particles of the positive electrode active material are induced to grow excessively, polarization may occur as the diffusivity of lithium ions decreases, and the possibility of cracks occurring in the particles increases due to the polarization.

[0141] Lithium secondary battery

[0142] According to another aspect of the present invention, a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector may be provided. The positive electrode active material layer may include a positive electrode active material according to various embodiments of the present invention. Therefore, the positive electrode active material is the same as that described previously, so for convenience, its specific description is omitted, and only the remaining structures not described above are described below.

[0143] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or the surface of aluminum or stainless steel may be treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to improve the binding force of the positive electrode active material. For example, it may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a nonwoven body.

[0144] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition including the positive electrode active material, a conductive material, and optionally a binder as required, on the positive electrode current collector.

[0145] In this case, the content of the positive electrode active material can be 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt % relative to the total weight of the positive electrode active material layer. When the positive electrode active material is included in the above content range, excellent capacity performance can be shown, but it is not limited thereto.

[0146] The above-mentioned conductive materials are used to impart conductivity to the electrode. In the battery formed, as long as they do not cause chemical changes and have electronic conductivity, they can be used without limitation. As specific examples, graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and one of them or a mixture of two or more thereof can be used. The above-mentioned conductive material may be included in an amount of 0.1% to 15% by weight relative to the total weight of the positive electrode active material layer.

[0147] The above-mentioned binder plays a role in improving the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the collector. As a specific example, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated ethylene propylene diene rubber, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, etc., can be used. One or a mixture of two or more thereof. Relative to the total weight of the positive electrode active material layer, 0.1% to 15% by weight of the above-mentioned binder may be included.

[0148] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can be prepared according to a common positive electrode preparation method. Specifically, it can be prepared by coating a positive electrode slurry composition on a positive electrode collector and then drying and rolling it. The above-mentioned positive electrode slurry composition is prepared by dissolving or dispersing the above-mentioned positive electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent.

[0149] The above-mentioned solvent may be a solvent commonly used in the art, and examples thereof include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water, and a mixture of one or more thereof may be used. Considering the coating thickness and preparation yield of the slurry, the amount of the above-mentioned solvent used is sufficient to dissolve or disperse the above-mentioned positive electrode active material, conductive material and binder and have a viscosity that can show excellent thickness uniformity when applied to prepare the positive electrode.

[0150] Furthermore, in another embodiment, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, and then laminating a thin film obtained by peeling the support on a positive electrode collector.

[0151] In addition, according to another aspect of the present invention, an electrochemical device comprising the positive electrode described above can be provided. Specifically, the electrochemical device described above can be a battery, a capacitor, etc., and more specifically, can be a lithium secondary battery.

[0152] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separation membrane and an electrolyte disposed between the positive electrode and the negative electrode. The positive electrode is the same as the above description, so for convenience, the specific description is omitted, and only the remaining configuration not described above is described below.

[0153] The lithium secondary battery may further include: a battery container for accommodating the electrode assembly of the positive electrode, the negative electrode and the separation membrane; and a sealing member for sealing the battery container.

[0154] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0155] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3 μm to 500 μm. Similar to the positive electrode current collector, the binding force of the negative electrode active material can be strengthened by forming fine concave and convex on the surface of the collector. For example, it can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven body.

[0156] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition including the negative electrode active material and a conductive material and optionally including a binder as required on the negative electrode collector.

[0157] As the negative electrode active material, a compound capable of reversibly inserting and extracting lithium can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; such as SiO β (0<β<2), SnO2, vanadium oxide, lithium vanadium oxide, metal oxides capable of being doped and dedoped with lithium; or composites containing the above metal compounds and carbon materials such as Si-C composites or Sn-C composites, etc., and one or a mixture of two or more of them can be used. In addition, as the above-mentioned negative electrode active material, a metal lithium film can also be used. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbons are soft carbon and hard carbon, and representative high-crystalline carbons are amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite (Kishgraphite), pyrolytic carbon (pyrolytic carbon), mesophase pitch based carbon fiber (mesophase pitch based carbon fiber), mesophase carbon microbeads (meso-carbon microbeads), mesophase pitch (Me sophase pitches) and petroleum or coal tar pitch derived cokes (petroleum or coal tar pitch derived cokes) and other high-temperature sintered carbons.

[0158] The negative electrode active material layer may contain 80 wt % to 99 wt % of the negative electrode active material, based on the total weight of the negative electrode active material layer.

[0159] The binder is a component that helps to bind the conductive material, the active material and the collector. Usually, based on the total weight of the negative electrode active material layer, 0.1 wt % to 10 wt % of the binder can be added. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber, sulfonated ethylene propylene diene rubber, styrene butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.

[0160] The conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the conductive material can be added in an amount of 10% by weight or less, preferably 5% by weight or less. There are no particular restrictions on such conductive materials as long as they do not induce chemical changes in the corresponding battery and have conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.

[0161] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it, wherein the negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent, or by casting the negative electrode slurry composition on a separate support and laminating a thin film obtained by peeling off the support on the negative electrode collector.

[0162] On the other hand, in the above-mentioned lithium secondary battery, the separation membrane is used to separate the negative electrode and the positive electrode and provide a mobile channel for lithium ions. As long as the separation membrane commonly used in the lithium secondary battery, it can be used without restriction, especially, preferably, for the ion movement of the electrolyte, the impedance is low and there is excellent electrolyte moisture-containing capacity. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers or their two or more layers of stacked structures. In addition, a common porous non-woven fabric can also be used, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a separation membrane coated with a ceramic component and a polymer substance can also be used, which can be selectively used with a single layer or multilayer structure.

[0163] Furthermore, examples of the electrolyte used in the present invention include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in preparing lithium secondary batteries.

[0164] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0165] As the above-mentioned organic solvent, any organic solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery can be used without limitation. Specifically, as the above-mentioned organic solvent, ester solvents such as methylacetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (EPC), etc. can be used. Carbonate solvents such as nate, PC, etc.; alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (r is a straight-chain, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane, etc. Among them, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate, etc.) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery, and low-viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be shown.

[0166] The above-mentioned lithium salt can be used without limitation as a compound that can provide lithium ions used in a lithium secondary battery. Specifically, the above-mentioned lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. Preferably, the concentration of the above-mentioned lithium salt is used in the range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore, excellent electrolyte performance can be shown, and lithium ions can be effectively moved.

[0167] When the electrolyte used herein is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a nitride solid electrolyte, or a halide solid electrolyte can be used, and preferably a sulfide solid electrolyte can be used.

[0168] As the material of the sulfide solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga and In) and S can be used. Examples of the above-mentioned sulfide solid electrolyte materials include Li2S-P2S5, Li2S-P2S-LiX (wherein X is a halogen element such as I or Cl), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are integers, Z is Ge, Zn or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (wherein p and q are integers, and M is P, Si, Ge, B, Al, Ga or In), etc.

[0169] The solid electrolyte, preferably a sulfide-based solid electrolyte, may be in an amorphous state, a crystalline state, or a mixed state of the amorphous state and the crystalline state.

[0170] Examples of materials for oxide-based solid electrolytes include Li7La3Zr2O 12 , Li 7-x Ln3Z 1-x Nb x O 12 , Li 7- 3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3、Li 1+x Al x Ti 2-x (PO4)3、Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, Li3+x PO 4-x N x (LiPON), Li 2+2x Zn 1-x GeO4(LISICON), etc.

[0171] The solid electrolyte may be arranged between the positive electrode and the negative electrode as a separate layer (solid electrolyte layer). In addition, the solid electrolyte may be partially contained in the positive electrode active material layer of the positive electrode independently of the solid electrolyte layer, or the solid electrolyte may be partially contained in the negative electrode active material layer of the negative electrode independently of the solid electrolyte layer.

[0172] In addition to the above electrolyte components, the electrolyte may further include one or more additives such as halogenated alkylene carbonate compounds such as bisfluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, etc., for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery. In this case, the above additives may be included in an amount of 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.

[0173] As described above, the lithium secondary battery containing the positive electrode active material of the present invention stably shows excellent discharge capacity, output characteristics and life characteristics, and can therefore be used in portable devices such as mobile phones, notebook computers, digital cameras, and electric vehicles such as hybrid electric vehicles (HEV).

[0174] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a prismatic shape, a pouch shape, a coin shape, etc. Also, preferably, the lithium secondary battery can be used not only as a battery cell used as a power source for small devices, but also as a unit battery of a medium or large battery module including a plurality of battery cells.

[0175] According to another aspect of the present invention, a battery module including the above-mentioned lithium secondary battery as a unit cell and / or a battery pack including the same may be provided.

[0176] The battery module or the battery pack can be used as a power tool; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle and a plug-in hybrid electric vehicle (PHEV); or a power source for one or more medium or large devices in a power storage system.

[0177] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only for illustrating the present invention, and the scope of the present invention should not be construed as being limited by these examples.

[0178] Preparation Example 1. Preparation of positive electrode active material

[0179] Example 1

[0180] A NiCoMn(OH)2 hydroxide precursor (Ni:Co:Mn=98:1:1 (atomic %)) was synthesized using nickel sulfate, cobalt sulfate, and manganese sulfate by a known co-precipitation method. The average particle size (D 50 ) is 3.0μm.

[0181] Next, the hydroxide precursor and LiOH (Li / (Ni+Co+Mn) molar ratio = 1.05) were mixed and heat treated (primary calcination) for 12 hours at 790° C. in an O2 atmosphere to obtain a lithium composite oxide. At this time, 1.0 mol% of NaOH and 0.1 mol% of ZrO2 were added as metal oxide-based dopants before the primary calcination.

[0182] After the primary calcination was completed, the above lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0183] Then, heat treatment (secondary calcination) was performed in an O 2 atmosphere at 700° C. for 12 hours to obtain a positive electrode active material containing a lithium composite oxide.

[0184] Example 2

[0185] A NiCoMn(OH)2 hydroxide precursor (Ni:Co:Mn=98:1:1 (atomic %)) was synthesized using nickel sulfate, cobalt sulfate, and manganese sulfate by a known co-precipitation method. The average particle size (D 50 ) is 3.0μm.

[0186] Next, the hydroxide precursor and LiOH (Li / (Ni+Co+Mn) molar ratio = 1.05) were mixed and heat treated (primary calcination) for 12 hours at 790° C. in an O2 atmosphere to obtain a lithium composite oxide. At this time, 2.0 mol% of NaOH and 0.1 mol% of ZrO2 were added as metal oxide-based dopants before the primary calcination.

[0187] After the primary calcination was completed, the above lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0188] Then, heat treatment (secondary calcination) was performed in an O 2 atmosphere at 700° C. for 12 hours to obtain a positive electrode active material containing a lithium composite oxide.

[0189] Example 3

[0190] A NiCoMn(OH)2 hydroxide precursor (Ni:Co:Mn=98:1:1 (atomic %)) was synthesized using nickel sulfate, cobalt sulfate, and manganese sulfate by a known co-precipitation method. The average particle size (D 50 ) is 3.0μm.

[0191] Next, the hydroxide precursor and LiOH (Li / (Ni+Co+Mn) molar ratio = 1.05) were mixed and heat treated (primary calcination) for 12 hours at 790° C. in an O2 atmosphere to obtain a lithium composite oxide. At this time, 3.0 mol % of NaOH and 0.1 mol % of ZrO2 were added as metal oxide-based dopants before the primary calcination.

[0192] After the primary calcination was completed, the above lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0193] Then, heat treatment (secondary calcination) was performed in an O 2 atmosphere at 700° C. for 12 hours to obtain a positive electrode active material containing a lithium composite oxide.

[0194] Comparative Example 1

[0195] A NiCoMn(OH)2 hydroxide precursor (Ni:Co:Mn=98:1:1 (atomic %)) was synthesized using nickel sulfate, cobalt sulfate, and manganese sulfate by a known co-precipitation method. The average particle size (D 50 ) is 3.0μm.

[0196] Next, the hydroxide precursor and LiOH (Li / (Ni+Co+Mn) molar ratio = 1.05) were mixed and heat treated (primary calcination) for 12 hours at 790° C. in an O2 atmosphere to obtain a lithium composite oxide. At this time, 4.0 mol% of NaOH and 0.1 mol% of ZrO2 were added as metal oxide-based dopants before the primary calcination.

[0197] After the primary calcination was completed, the above lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0198] Then, heat treatment (secondary calcination) was performed in an O 2 atmosphere at 700° C. for 12 hours to obtain a positive electrode active material containing a lithium composite oxide.

[0199] Comparative Example 2

[0200] A NiCoMn(OH)2 hydroxide precursor (Ni:Co:Mn=98:1:1 (atomic %)) was synthesized using nickel sulfate, cobalt sulfate, and manganese sulfate by a known co-precipitation method. The average particle size (D 50 ) is 3.0μm.

[0201] Next, the hydroxide precursor and LiOH (Li / (Ni+Co+Mn) molar ratio = 1.05) were mixed and heat treated (primary calcination) for 12 hours at 790° C. in an O2 atmosphere to obtain a lithium composite oxide. At this time, 5.0 mol% of NaOH and 0.1 mol% of ZrO2 were added as metal oxide-based dopants before the primary calcination.

[0202] After the primary calcination was completed, the above lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0203] Then, heat treatment (secondary calcination) was performed in an O 2 atmosphere at 700° C. for 12 hours to obtain a positive electrode active material containing a lithium composite oxide.

[0204] Comparative Example 3

[0205] A NiCoMn(OH)2 hydroxide precursor (Ni:Co:Mn=98:1:1 (atomic %)) was synthesized using nickel sulfate, cobalt sulfate, and manganese sulfate by a known co-precipitation method. The average particle size (D 50 ) is 3.0μm.

[0206] Next, the hydroxide precursor and LiOH (Li / (Ni+Co+Mn) molar ratio = 1.05) were mixed and heat treated (primary calcination) at 790°C for 12 hours in an O2 atmosphere to obtain a lithium composite oxide. At this time, 5.0 mol% of NaOH was added before the primary calcination.

[0207] After the primary calcination was completed, the above lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0208] Then, heat treatment (secondary calcination) was performed in an O 2 atmosphere at 700° C. for 12 hours to obtain a positive electrode active material containing a lithium composite oxide.

[0209] Preparation Example 2. Fabrication of a lithium secondary battery (half-cell)

[0210] 94 wt % of each positive electrode active material prepared according to Preparation Example 1, 3 wt % of carbon black and 3 wt % of PVDF binder were dispersed in 30 g of N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum film having a thickness of 15 μm and vacuum dried at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0211] Relative to the above-mentioned positive electrode, lithium foil is used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25μm) is used as a separation membrane, and an electrolyte solution containing LiPF6 at a concentration of 1.15M in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7 is used to prepare a half-cell.

[0212] Experimental Example 1. Particle size distribution analysis of positive electrode active material

[0213] The particle size distribution of the lithium composite oxide in each positive electrode active material prepared according to Preparation Example 1 was analyzed using a known laser diffraction method. Specifically, after each positive electrode active material was dispersed in a dispersion medium, a laser diffraction particle size measuring device (Microtrac MT 3000) was used to irradiate an ultrasonic wave of about 28 kHz at a power of 60 W to obtain a volume cumulative particle size distribution diagram.

[0214] Then, the particle sizes corresponding to 10%, 50% and 90% of the volume cumulative amount, the minimum particle size in the volume cumulative particle size distribution diagram, and the maximum particle size in the volume cumulative particle size distribution diagram are obtained from the volume cumulative particle size distribution diagram.

[0215] The above analysis results are shown in Tables 1 and 2 below.

[0216] Table 1

[0217] Classification <![CDATA[D min ]]> <![CDATA[D 10 ]]> <![CDATA[D 50 ]]> <![CDATA[D 90 ]]> <![CDATA[D max ]]> Example 1 2.5 3.1 6.5 12.7 14.4 Example 2 2.6 3.0 5.6 11.1 12.7 Example 3 2.6 3.1 6.1 10.5 11.6 Comparative Example 1 2.9 3.6 7.8 11.9 12.9 Comparative Example 2 3.2 4.2 9.4 14.6 15.8 Comparative Example 3 1.5 3.5 8.8 17.0 30.0

[0218] Table 2

[0219]

[0220] Referring to the results in Table 1 and Table 2, it can be confirmed that the particle size distribution peak of the positive electrode active materials according to Examples 1 to 3 is oriented toward D 0 which is the maximum particle size, as compared with the positive electrode active material according to Comparative Example 3. max The particle size distribution peak is highly sharp.

[0221] On the other hand, in the case of the positive electrode active materials according to Comparative Examples 1 and 2, the particle size distribution peak is oriented toward D 0 which is the maximum particle size, as compared with the positive electrode active materials according to Examples 1 to 3. max Excessive side deviation.

[0222] Experimental Example 2. XRD analysis of positive electrode active material

[0223] The positive electrode active material prepared according to Preparation Example 1 (Examples 1 to 3, Comparative Examples 1 and 2) was subjected to X-ray diffraction (XRD) analysis to calculate the full width at half maximum (FWHM) of the peaks belonging to the (003) plane and the (104) plane. In addition, the a-axis length, c-axis length and grain size of the grains obtained by Rietveld analysis of the above XRD analysis results were calculated. By using Cu-Kα radiation XRD analysis was performed using a Bruker D8 Advance diffractometer.

[0224] The above XRD analysis results are shown in Table 3 below.

[0225] Table 3

[0226] Experimental Example 3. Evaluation of electrochemical performance of lithium secondary battery (half-cell)

[0227] The lithium secondary battery (half-cell) prepared according to Preparation Example 2 was subjected to a charge / discharge experiment using an electrochemical analyzer (Toyo, Toscat-3100) at 25°C, a voltage range of 3.0 V to 4.3 V, and a discharge rate of 1.0 C / 0.1 C to measure the initial charge capacity, initial discharge capacity, initial efficiency, and 1.0 C / 0.1 C rate performance.

[0228] In addition, the same lithium secondary battery (half-cell) was charged / discharged 50 times at 45°C, a voltage range of 3.0 V to 4.3 V, and 1C / 1C using an electrochemical analyzer (Toyo, Toscat-3100), and then the ratio of the discharge capacity at the 50th cycle (cycle capacity retention) was measured.

[0229] The above measurement results are shown in Table 4 below.

[0230] Table 4

[0231]

[0232] Referring to the results in Table 4 above, it can be confirmed that compared with the lithium secondary battery using the positive electrode active material according to Comparative Example 3, the lithium secondary batteries using the positive electrode active materials according to Examples 1 to 3 do not seem to have reduced capacity, while the rate performance and life performance are improved.

[0233] In addition, it can be confirmed that the particle size distribution peak is D, which is the maximum particle size. max Compared with Comparative Examples 1 and 2, which have a side shift, the lithium secondary batteries using the positive electrode active materials according to Examples 1 to 3 have higher capacity performance, rate performance, and life performance.

[0234] Although the embodiments of the present invention are described above, those skilled in the art will understand that various modifications and changes can be made to the present invention by adding, modifying, deleting, increasing, etc., without departing from the scope of the idea of ​​the present invention as described in the claims, and these also fall within the scope of the rights of the present invention.

Claims

1. A positive electrode active material, comprising a lithium composite oxide capable of inserting and extracting lithium, wherein the positive electrode active material is characterized in that: The lithium composite oxide contains at least lithium and a transition metal. The lithium composite oxide satisfies the following formula 1 and formula 2: [Formula 1] D max ≤15μm [Formula 2] D 90 -D 50 >D 50 -D 10 (In the above formula 1 and formula 2, in the volume cumulative particle size distribution diagram obtained by laser diffraction particle size distribution measurement, the particle size of 10% of the volume cumulative amount is D 10 , the particle size at which 50% of the volume accumulation occurs is D 50 , the particle size at which 90% of the volume accumulation occurs is D 90 The minimum particle size of the above volume cumulative particle size distribution diagram is D min The maximum particle size of the above volume cumulative particle size distribution diagram is D max ).

2. The positive electrode active material according to claim 1, characterized in that The lithium composite oxide satisfies the following formula 3: [Formula 3] 4.2μm<D 90 -D 50 <8.2μm。 3. The positive electrode active material according to claim 1, characterized in that The lithium composite oxide satisfies the following formula 4: [Formula 4] 2μm<D 50 -D 10 <4μm。 4. The positive electrode active material according to claim 1, characterized in that The lithium composite oxide satisfies the following formula 5: [Formula 5] 1.2≤(D 90 -D 10 ) / D 50 ≤1.5。 5. The positive electrode active material according to claim 1, characterized in that The lithium composite oxide satisfies the following formula 6: [Formula 6] 1.2≤(D max -D 50 ) / (D 50 -D min )≤2.7。 6. The positive electrode active material according to claim 1, characterized in that The transition metal is at least one selected from nickel, cobalt, manganese and aluminum.

7. The positive electrode active material according to claim 1, characterized in that The lithium composite oxide is represented by the following chemical formula 1: [Chemical formula 1] The a Nor 1-(b+c+d) Co b M1 c M2 d O2 in, M1 is at least one selected from Mn and Al, M2 is at least one selected from Na, K, Mg, Ca, Ba, Mn, B, Ce, Hf, Ta, Cr, F, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd and Cu, M1 and M2 are different from each other. 0.5≤a≤1.5, 0≤b≤0.20, 0≤c≤0.30, 0≤d≤0.

10.

8. The positive electrode active material according to claim 1, characterized in that In the above Chemical Formula 1, b+c+d is 0.30 or less.

9. The positive electrode active material according to claim 1, characterized in that The lithium composite oxide exists in at least one form selected from a single particle and a secondary particle formed by aggregation of a plurality of primary particles.

10. The positive electrode active material according to claim 9, characterized in that The secondary particles are in a state where two to ten primary particles are aggregated.

11. The positive electrode active material according to claim 1, characterized in that In an X-ray diffraction analysis of the positive electrode active material using Cu—Kα rays, the full width at half maximum (FWHM) of the diffraction peak attributed to the (104) plane is 0.080 or more and 0.11 or less.

12. The positive electrode active material according to claim 1, characterized in that The c-axis length of the crystallites obtained by Rietveld analysis of X-ray diffraction of the positive electrode active material is the following.

13. The positive electrode active material according to claim 1, characterized in that The size of crystallites obtained by Rietveld analysis of X-ray diffraction of the positive electrode active material is 147 nm or more and 162 nm or less.

14. A positive electrode, characterized in that: The positive electrode active material comprises the positive electrode active material according to any one of claims 1 to 13.

15. A lithium secondary battery, characterized in that: The positive electrode according to claim 14 is used.

Citation Information

Cited By

  • Method for preparing single-crystal-state lithium-rich manganese-based positive electrode material by molten salt method, positive electrode material prepared by method, positive electrode and battery

    CN120914242A